International consensus statement on the use of uterotonic agents during caesarean section. (25th July 2019) - Heesen, M.; Carvalho, B.; Carvalho, J. C. A.; Duvekot, J. J.; Dyer, R. A.; Lucas, D. N.; McDonnell, N.; Orbach‐Zinger, S.; Kinsella, S. M.
Summary: It is routine to give a uterotonic drug following delivery of the neonate during caesarean section. However, there is much heterogeneity in the relevant research, which has largely been performed in low‐risk elective cases or women with uncomplicated labour. This is reflected in considerable variation in clinical practice. There are significant differences between dose requirements during elective and intrapartum caesarean section. Standard recommended doses are higher than required, with the potential for acute cardiovascular adverse effects. We recommend a small initial bolus dose of oxytocin, followed by a titrated infusion. The recommended doses of oxytocin may have to be increased in women with risk factors for uterine atony. Carbetocin at equipotent doses to oxytocin has similar actions, while avoiding the requirement for a continuous infusion after the initial dose and reducing the need for additional uterotonics. As with oxytocin, carbetocin dose requirements are higher for intrapartum caesarean sections. A second‐line agent should be considered early if oxytocin/carbetocin fails to produce good uterine tone. Women with cardiac disease may be very sensitive to the adverse effects of oxytocin and other uterotonics, and their management needs to be individualised.